Design of R.C.C. Framed Structure Considering the Effect of Stiffness of Slab - Bhojram; Nirmal, Pradeep Kumar; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2022)
The slab is very important member in building and slab is one of the largest member consuming concrete. When the load acting on the slab is large or clear span between columns is more the slab thickness is on increasing. It leads to consume more material such as concrete and steel, due to that self-weight of slab is increase. So the self-weight of slab can be reducing by considering the stiffness of slab. Stiffness indicates the capacity of the structure to resist deformation. The aim of this research is to understand the behavior of moments induced in the columns when the stiffness of slab is considered. The present paper mainly focused on the behavior of the effect of floor slabs in the frame due to vertical loading and the moments induced in columns. STAAD software has been used to model the frame with and without considering the effect of stiffness of slab.